DINAMIKA MODEL EPIDEMIK SVIRS TERHADAP PENYEBARAN PENYAKIT INFLUENZA DENGAN STRATEGI VAKSINASI KONTINU - -, SALMAH; Marentek, Tonaas K.W.Y.; Afri, Lusi Eka (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The research about dinamica model epidemic SVIRS by continous vaccination strategy in sread of influenza used mathematical models. The result gots free of disease equilibrium (